(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study focuses on women empowerment through higher education to change in economic status of women in TamilNadu. Better human progress is guaranteed by women’s education, which also serves to educate those born after that age. Education is a key component of women’s empowerment since it empowers them to respond to challenges, challenge conventional beauty standards, and disrupt their way of life. Since educated women may play a crucial role in the advancement of the country, women’s education in India has also been a notable diversion for the government and general public. From the start, Tamil Nadu has been crucial to the expansion and advancement of women’s education. Women’s education is significantly more important than men’s. According to Mahatma Gandhi, women’s education serves the family as a whole, whereas men’s education is geared towards the individual. Higher levels of education among women are positively correlated with more decision-making autonomy across a range of domains. Education is a crucial component of women’s empowerment since it gives them the tools they need to face obstacles, question their traditional roles, and make life. Therefore, we cannot undervalue the significance of education in light of Tamil Nadu’s recent rise to prominence and the empowerment of women. Women’s education is one of the most effective means of influencing their status in society. These interventions refer to increasing education and income opportunities for women that might increase their decision-making power as well as their development in Tamil Nadu. In this context, education also reduces inequality and serves as a means of improving their status within the family’s growth and development.